Current Status of Management on Pharmacopuncture in Korea through Introduction of an Accreditation System - Sung, Soo-Hyun; Shin, Byung-Cheul; Park, Min-Jung; Kim, Kyeong Han; Kim, Ji-Won; Ryu, Ji-Yeon; Park, Jang-Kyung (Journal of pharmacopuncture, 2019)
Pharmacopuncture is a new form of acupuncture treatment that injects herbal medicine into acupuncture points. This paper introduces the management status of pharmacopuncture through accreditation, and examines the effect of accreditation on pharmacopuncture management. The Accreditation System of External Herbal Dispensaries (EHDs) of traditional Korean medicine clinics announced by the Ministry of Health and Welfare in September 2018 were investigated. The Accreditation System of EHDs assesses and certifies herbal medicine and pharmacopuncture preparations. Regular components for the 'pharmacopuncture' certification consist of nine standards, 30 categories, and 165 items. The nine standards include: herbal dispensary facilities, clean room management, management and organization operation, employee management, document management, continuous quality control, herbal medicine management, management of preparation, and pavement management. Through EHD accreditation and certification system, traditional Korean medicine clinics and EHDs can now manage pharmacopuncture medicine quality and promise safe pharmacopuncture treatment for the people.